PHONEMIC AWARENESS AMONG RURAL PRIMARY SCHOOL ENGLISH LANGUAGE TEACHERS IN SARAWAK - Joseph, Ramanair; Chen, Siaw We; Soubakeavathi, Rethinasamy; Jecky, Misieng; Ambigapathy, Pandian (AESS Publications, 2020)
Reading is an important skill that needs to be developed from young among children. In supporting them to read, they will first need to learn to decode which involves understanding the alphabetic principle of the written word which is that letters characterise sounds or phonemes. Developing phonemic awareness requires explicit teaching that is systematic and thus, teachers play an important role. This study thus, uncovers the knowledge of phonemic awareness of rural primary school teachers of English as a Second Language (ESL) and their related instructional practices. Data were collected through a semi-structured questionnaire which was completed by five ESL teachers from a rural primary school in Sarawak. The findings revealed that the teachers had limited knowledge of phonemic awareness. Although two of them reported focussing their instructional approaches to develop their students’ phonemic awareness, their self-assessment of this knowledge was low. This limited knowledge would not only affect the design of their instructional practices but also impede the reading success of young ESL learners.